Pementasan Tari Kincang-Kincung Dalam Upacara Piodalan Pura Puseh Kaja Di Desa Tunjuk, Kabupaten Tabanan - I Made Novianta (Pramana: Jurnal Hasil Penelitian, 2021)
The Kincang-Kincung dance in Tunjuk Village, Tabanan Regency has its own uniqueness, starting from the movement, the ceremonial facilities used and this dance has magical powers so that the dancers experience a trance. Kincang-Kincung dance is closely related to piodalan at Puseh Kaja Temple, Tunjuk Village. From the results of research on Kincang-Kincung Dance in Tunjuk Village, Tabanan Regency, the following results were obtained: 1) the reason for performing the Kincang Kincung dance at the Piodalan ceremony at Puseh Kaja Temple, Tunjuk Village, Tabanan Regency, namely mythological reasons, namely in the form of ancestral worship, Theological Reasons as a means of expressing a sense of devotion, sociological reasons as a means of interacting with fellow people, and philosophical reasons as a form of gratitude for the people of Tunjuk Village. The form of Kincang-Kincung Dance is explained through the dancers, the dance movements, the venue for the performance, the make-up and clothing, the time of the performance, the ceremony facilities, percussion accompaniment, and the series of Kincang Kincung dance performances. The Kincang Kincung dance performance has a ritual function as an offering to be grateful for the gift of Ida Sang Hyang Widhi Wasa. Its social function is as a means of unifying and establishing the brotherhood of the accompanying community. The function of preserving the culture of the Kincang Kincung dance performance is a vehicle for preserving artistic and cultural values in Bali and in the village of Tunjuk in particular. An aesthetic function, because this kincang kincung dance fulfills several aesthetic elements that can evoke a sense of beauty for the audience.